(untitled) (GAIMS Journal of Medical Sciences, 2024)
Background: Biofilms are the assembly of bacterial species embedded in an extra-polymer matrix. Literature suggests biofilms can be formed on various biotic and abiotic surfaces. This may contribute to diseases by inducing chronic inflammation by underlying bacterial species. A prospective observational study was planned to isolate and identify bacterial pathogens among heterogenous clinical samples along with their antimicrobial resistance pattern and to study their tendency to form biofilm. Materials and Methods: Samples were processed and identified according to standard microbiological protocol. Further Tissue Culture Plate (TCP) method was employed for detection of biofilm formation. Data analysis was done using descriptive statistics, Chi-square test & Fisher test. Results: Among 329 positive bacterial isolates, 295 isolates were gram negative while only 35 isolates were gram positive. 138 (41.95%) bacterial isolates produced biofilm while 191 (58.05%) isolates were non-biofilm producers. Antibacterial resistance was higher in biofilm producing isolates as compared to non-biofilm producing isolates. Conclusions: Timely information about biofilm producing bacterial species causing infection can help clinicians for appropriate treatment measures in addition to antibiotic therapy. Knowledge regarding these organisms could help us in formulating hospital antibiotic policy which will lead to better patient outcome.